Adopting the TRC Model to Enhance Students’ Revision Competence in Translation Classes - Arso Setyaji; Rahmawati Sukmaningrum; Faiza Hawa (Soegijapranata Catholic University, 2025)
Translation revision is one of required competences for learners who intend to become translators as their professional choice. It becomes an important step in translation workflow. This competence should be owned by translators or aspiring translators. Unfortunately, revision competence is almost never given in translation class. Almost all courses in translation focuses on the students’ competence in translating, but ignores the competence of revising translated text. This study, therefore, applied a learning form named TRC (Translation Revision Competence) model in translation class of Universitas PGRI Semarang that will equip students in translation competence. To verify the hypothesis about the nature of TRC, this study used a pretest - posttest design, with an experimental group and a control group. To collect the data needed in this research, researchers used assignments, documents and questionnaires. Based on the calculation of the paired sample T-test in this research, the results of Sig. (2-tailed) were 0.001 where the results were smaller than 0.050 (0.050). As the initial hypothesis of the study set by the researcher where if Sig. (2-tailed) 0.050 then the hypothesis is accepted, the researcher concludes that there is a significant difference in the quality of the revised text of students/participants who received TRC training compared to those who did not receive TRC training. From these results, it is concluded that the TRC model has a positive impact on the level of quality and ability to revise students' translated texts in the Translation class